1983
DOI: 10.1002/kin.550150106
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the reactions of O3 and OH radicals with furan and thiophene at 298 ± 2 K

Abstract: Rate constants for the reactions of 0 3 and OH radicals with furan and thiophene have been determined at 298 f 2 K. The rate constants obtained for the 0 3 reactions were (2.42 f 0.28) X 1O-lS cm3/molec.s for furan and <6 X cm3/molec-s for thiophene. The rate constants for the OH radical reactions, relative to a rate constant for the reaction of OH radicals with n-hexane of (5.70 f 0.09) X cm3/molec.s, were determined to be (4.01 f 0.30) X lo-" cm3/molec.s for furan and (9.58 f 0.38) X 10-l2 cm3/molec.s for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
87
0

Year Published

1983
1983
2011
2011

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(99 citation statements)
references
References 38 publications
12
87
0
Order By: Relevance
“…In the temperature range 292-390 K the agreement between the absolute and relative rate studies is good. The room temperature relative rate data of Atkinson et al (1983a), , Behnke et al (1987Behnke et al ( , 1988 and McLoughlin et al (1993), which are not shown in the Arrhenius plot in Fig. 11, are also in good agreement with these data of Atkinson et al (1982a), Klein et al (1984), Donahue et al (1998) and DeMore and Bayes (1999).…”
Section: Oh+n-hexanesupporting
confidence: 74%
“…In the temperature range 292-390 K the agreement between the absolute and relative rate studies is good. The room temperature relative rate data of Atkinson et al (1983a), , Behnke et al (1987Behnke et al ( , 1988 and McLoughlin et al (1993), which are not shown in the Arrhenius plot in Fig. 11, are also in good agreement with these data of Atkinson et al (1982a), Klein et al (1984), Donahue et al (1998) and DeMore and Bayes (1999).…”
Section: Oh+n-hexanesupporting
confidence: 74%
“…The experimental technique has been described previously [7,9] and was essentially identical to that used for the determination of OH radical rate constants for a series of acyclic alkenes [9]. Hence only the relevant details are given here.…”
Section: Methodsmentioning
confidence: 99%
“…(1) OH + alkene -products (2) OH + isoprene -products Provided these organics are consumed only by reaction with OH radicals (see later) and since dilution due to sampling is avoided by use of a collapsible Teflon reaction bag, then [7,9] Irradiations were carried out in a -60-L cylindrical Teflon reaction bag surrounded by 24 GE F15T8-BL 15-W blacklights. In this work eight of these blacklights were used, corresponding to a photolytic half-life of CH3ONO of -30 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study of the reactions of OH radicals with a series of cyclic and polycyclic alkanes, where the reactions proceed via H-atom abstraction, it was observed [9] that ring strain energies in excess of -5 kcal/mol led to a decrease in the rate constants relative to those expected for the strainfree molecules. For the addition reactions of 0 3 and OH radicals, however, data are available only for a small number of cycloalkenes [7,8].…”
Section: Introductionmentioning
confidence: 94%